Analysis of Multi-Objective of Farmers’ Production in Small Scale Maize/Cowpea Farms in Nasarawa State, Nigeria - Suleiman, H/R; Ishiak, O.K. (Canadian Journal of Agriculture and Crops, 2019)
This study examined the utilization of farm resources and multi-objectives of small scale maize / cowpea farmers. Data were collected from a randomly sample of 120 farmers from six local government areas randomly selected from the study area. These were analysed using regression analysis, gross margin and pair comparism method. The result revealed the cost of production of small scale maize/cowpea farmers was N24,145.70 per hectare and realized revenue of N39, 785.04 per hectare. The mean return over total cost of production is N15, 639.34 and the cost-benefit ratio of 0.61. The regression result of socio economic variables showed a positive and significant influence of farm size (P<0.01), age (P<0.01) and household size (P<0.1) on the amount of maize/cowpea yield. The coefficient of land and seed are positive and statistically significant (P<0.05), indicating a direct relationship between them and total farm output. The ranking of satisfying family food requirement and provision of self employment over the other objectives were statistically different at 5% with an LSD = 20.09. Therefore, government policies and programmes should be redirected with the aim of boosting farmers production ability in order to enhance their farm capital expansion rather than just satisfying family food requirement.